Asuhan Kebidanan Pada Ibu Bersalin Primigravida Dengan Partus Lama Di Klinik Pratama Siti Kholijah JL. Marelan I, Terjun, Kec. Medan Marelan - Rahmawani Fauza (CV. Pusdikra Mitra Jaya, 2024)
Prolonged labor is labor that lasts more than 24 hours in primi, and more than 18 hours in multi.(Murnika, 2015) Globally, about 8-11% of pregnant women experience abnormalities in the 1st stage of labor. Delayed labor in the active phase was found in 25% of nulliparous women and 15% of multiparous women. A study in Sweden found that 23% of patients about to go into labor experienced a delay in progress in the latent phase. The study also found that the delay in progress was more common in nulliparous women than multiparous women (29.2% vs. 17). Long parturition is one of the contributors to maternal mortality in the world, based on WHO in 2014 there were cases of prolonged labor in women in the world, namely 289 per 100,000 live births. Meanwhile, in Indonesia, the incidence of prolonged labor is the highest in ASEAN, namely 359 per 100,000 live births, mothers die from prolonged labor (WHO, 2014). Researchers provide comprehensive midwifery care for pregnant women, maternity, postpartum, BBL, neonates and family planning using a midwifery management approach to Mrs